The Role of Nursing in the Promotion of Mental Health: Innovative Strategies for the Comprehensive Approach to Patients - Liliana Alexandra Ríos García1, Andrea Cristina Torres Jara2, Miriam Iralda Piray Inga3 (Journal of International Crisis and Risk Communication Research, 2024)
A documentary review was carried out on the production and publication of research papers related to the study of the variables Nursing, Mental Health and Patient Care. The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2018-2023 by Latin American institutions with respect to the study of the aforementioned variables, achieving the identification of 193 publications in total. The information provided by this platform was organized through graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors regarding the proposed theme is referenced through a qualitative analysis. Among the main findings made through this research, it is found that Brazil, with 129 publications, was the Latin American country with the highest scientific production registered in the name of authors affiliated with institutions in that nation. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material related to the study of Nursing, Mental Health and Patient Care was Nursing with 101 published documents, and the Type of Publication that was most used during the period indicated above was the Journal Article, which represents 89% of the total scientific production.